Acute Abdomen Due to Uncontrolled Use of Warfarin: Spontaneous Intra-abdominal - Fatih Dal; Hasan Ökmen; Turgay Erginel; Meltem Küçük Yılmaz; Önder Akkuş; Serkan Sarı (Haseki Tıp Bülteni, 2017)
Warfarin is an oral anticoagulant, which is commonly used in the treatment and prophylaxis of thromboembolic conditions. Bleeding is the primary adverse effect associated with warfarin. The majority of warfarin-related bleedings are spontaneous minor hemorrhages occurring in the subcutaneous or intramuscular tissues and can be treated by decreasing the dose of oral anticoagulants. However, although rare, it is possible to encounter spontaneous major bleedings with increased risk of mortality. Conservative approach is the preferred initial therapy for hemodynamically stable patients with major intra-abdominal hemorrhages that we define as the intermediate group patients. Nevertheless, surgery is required for hemodynamically unstable patients with acute abdominal pain in cases of ongoing active hemorrhage, generalized peritonitis, obstruction, acute abdomen, intestinal ischemia, and perforation. In this article, we present a rare case of acute abdomen and spontaneous intra-abdominal hemorrhage resulting from uncontrolled use of warfarin and a new classification requirement.